THE CONSTITUTIONALITY OF THE ESTABLISHMENT OF THE LAW ON THE INSTITUTION OF THE PEOPLE'S CONSULTATIVE ASSEMBLY (MPR) OF THE REPUBLIC OF INDONESIA AS A FORM OF MANIFESTATION OF ARTICLE 2 PARAGRAPH (1) OF THE 1945 CONSTITUTION OF THE REPUBLIC OF INDONESIA - Monitasari, Restu Gusti (Universitas Dharmawangsa Medan, 2025)
This study discusses two main problems: first, constitutional values in the institutional arrangements of People's Consultative Assembly of the Republic of Indonesia (MPR RI) based on the 1945 Constitution of the Republic of Indonesia in the development of legislation in Indonesia; second, the urgency of the establishment of the MPR RI Institutional Law as an implementation of Article 2 paragraph (1) of the 1945 Constitution of the Republic of Indonesia. The article states that